Secretion of salivary glands of the Brazilian termite Serritermes serrifer Hagen & Bates (Isoptera : Serritermitidae) - Costa-Leonardo, Ana Maria [UNESP] (My University, 1997)
The salivary glands of termites are composed of several secretory acini connected by ducts. These glands, in the Brazilian termite Serritermes serrifer, were examined through the electron microscope. The ultrastructure of worker salivary acinus revealed central ductule cells and four different types of cells. Cells of type I contain an abundance of electron-lucid vacuoles of various sizes which fuse to form enormous vacuolar structures that fill up most of the cell. Cells of type II are narrow cells in which the secretion is contained in small clear vacuoles of approximately equal diameter. Both of these cellular types have numerous Golgi bodies and rough endoplasmic reticulum. Type III or parietal cells have an apical plasma membrane deeply infolded and lined by microvilli. This type of cell is located in the acinar periphery and occurs in pairs. Cells of type IV are completely filled with electrondense secretion. The secretory granules can be small in some cells or large and similar to fingerprints in others. This is the first report of the occurrence of these spiral or concentric rings of dense material in the salivary gland of Isoptera.